The Effect of Coconut Fibres, Banana Trunk Peel and Baggasse on the Lost Circulation of the Drilling Mud - Rizki Akbar; Abdul Hamid; Ratnayu Sitaresmi (Penerbitan Universitas Trisakti, 2019)
Lost Circulation Materials (LCM) are specially designed not to damage the penetrating formation during handling of loss circulation problems and are very effective for drilling operations worldwide. Optimization of LCM composition may stop loss circulation effectively and protect the production zone from the invasion of mud filtrate. The concentration of lost circulation materials (LCM) is a key parameter to determine the effectiveness of LCM. In this study, laboratory equipment such as the Hamilton beech mixer, Fann VG meter and API filter press are used to evaluate the effectiveness of various LCMs in dealing with loss circulation. In this research, coconut fibre, banana tree skin, and bagasse are used as LCM in various concentrations. The mud losses were simulated using an 80 mesh shaker. The quality of the muddy rheological properties wasthe basic parameters to be evaluated. The test was carried out at 80oF and 200oF. The experimental results show that bagasse has the best performance both at 80oF and 200oF as LCM compared withcoconut fibres and banana trunk. The lost circulation of mud filtrate at 80oF and 200oF due to the addition of 2 gram bagasse is 34 ml and 40 ml, respectively.